National reference centiles of anthropometric indices and BMI cut-off values in a child population in Nepal - Saujanya Karki; Jari Päkkilä; Marja-Liisa Laitala; Marja Ojaniemi; Vuokko Anttonen (Annals of Human Biology, 2018)
Background: There is a need for national- or ethnicity-specific growth reference values in developing countries like Nepal, where rapid urbanisation and consequential nutritional transition is taking place. Aim: To establish national growth reference percentiles for anthropometric indices and to propose body mass index (BMI) cut-off values for Nepalese schoolchildren. Methods: This study comprised 1135 Nepalese schoolchildren of four World Health Organization (WHO) indexed age groups (5-, 6-, 12- and 15-year-olds). The age- and gender-specific smoothed percentile curves for anthropometric indices (height, weight, BMI, waist circumference, waist-to-hip-ratio and waist-to-height-ratio) were constructed using LMS method and the corresponding Z-scores were computed. The Receiver Operating Characteristic analysis was used to determine BMI cut-off values based on the International Obesity Taskforce (IOTF) and the WHO growth references. Results: The age- and gender-specified smoothed percentile values of anthropometric indices at 3rd, 10th, 25th, 50th, 75th, 90th and 97th percentiles were computed. The BMI cut-off values for thinness (−1.2 SDS/12th percentile), overweight (+1.2 SDS/88th percentile) and obesity (+2.1 SDS/98th percentile) had high discriminating power, and high sensitivity and specificity. Conclusion: The Nepali anthropometric cut-off values proposed here can be recommended to be applied into research, and to identify public health risks in Nepal among these age groups.